Moral disengagement in harmful but cherished food practices? An exploration into the case of meat - Graça, J.; Calheiros, M. M.; Oliveira, A. (Journal of Agricultural and Environmental Ethics, 2014)
Harmful but culturally cherished practices often endure in spite of the damages they cause. Meat consumption is increasingly becoming one of such cases and may provide an opportunity from which to observe these phenomena. Growing evidence indicates that current and projected production and consumption patterns are important contributors to significant environmental problems, public health degradation, and animal suffering. Our aim is to contribute to a further understanding of the psychological factors that may hinder or promote personal disposition to change food habits to benefit each of these domains. Drawing from previous evidence, this study explores the proposition that some consumers are motivated to resort to moral disengagement strategies when called upon to consider the impacts of their food habits. Data were collected from six semi-structured focus groups with a sample of 40 participants. Although affirming personal duties towards preserving the environment, promoting public health, and safeguarding animal welfare, participants did not show personal disposition to change their meat consumption habits. Several patterns of response that resonate with the principles of moral disengagement theory (i.e. reconstrual of the harmful conduct; obscuring personal responsibility; disregard for the negative consequences; active avoidance and dissociation) were observed while discussing impacts and the possibility of change. Results seem to support the proposition that the process of moral disengagement may play a role in hindering openness to change food habits for the benefit of the environment, public health, and animals, and point towards the relevance of further exploring this approach.